1993
DOI: 10.1037/0278-7393.19.2.405
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced feeling of recognition: Effects of identifying and manipulating test items on recognition memory.

Abstract: This study showed that regardless of its actual status, a test item was more likely to be judged as old if, before making an old-new judgment, subjects attempted to (a) identify a test word or a test picture's name (Experiments 1 and 2), or (b) to work on a normally presented test word, such as reversing the letter order of the word or constructing a word that rhymed with the test word (Experiment 3). Experiment 1 replicated the enhanced feeling of recognition effect reported by M. Watkins and Z. F. Peynirciog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
85
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 21 publications
5
85
1
Order By: Relevance
“…Thus, subjects act as if perceptual fluency was a valid guide to oldness. Previous demonstrations of the importance of perceptual fluency in recognition memory judgments have all been based on changing subjects' criteria rather than on changing their discrimination between old and new items (e.g., Jacoby & Whitehouse, 1989;Luo, 1993;Whittlesea, Jacoby, & Girard, 1990). For example, Luo (1993) reported evidence that both perceptual and conceptual fluency affected subjects' tendencies to classify an item as old and showed that this effect was completely attributable to changes in response bias and not to changes in d'.…”
Section: Fluency In Recognition Memory 381mentioning
confidence: 97%
“…Thus, subjects act as if perceptual fluency was a valid guide to oldness. Previous demonstrations of the importance of perceptual fluency in recognition memory judgments have all been based on changing subjects' criteria rather than on changing their discrimination between old and new items (e.g., Jacoby & Whitehouse, 1989;Luo, 1993;Whittlesea, Jacoby, & Girard, 1990). For example, Luo (1993) reported evidence that both perceptual and conceptual fluency affected subjects' tendencies to classify an item as old and showed that this effect was completely attributable to changes in response bias and not to changes in d'.…”
Section: Fluency In Recognition Memory 381mentioning
confidence: 97%
“…This effect is found for both studied and nonstudied words, and revelation can take many forms, such as presenting the words as anagrams or with rotated letters (e.g., Watkins & Peynircio lu, 1990). The study and test items can be in different modalities (e.g., Luo, 1993), and the effect is seen with nonverbal materials (Bornstein & Wilson, 2004;Tekcan & Peynircio lu, 2001), as well. Finally, the revealed items do not have to be the ones on which the recognition decision is made or even to be related to the studied words (Westerman & Greene, 1996).…”
mentioning
confidence: 99%
“…Briefly, although their proposed mechanisms differ, some explanations of this intriguing effect say that revealing an item increases its perceived familiarity or the familiarity of the following to-be-recognized item (e.g., Luo, 1993;Westerman & Greene, 1998;Whittlesea & Williams, 2001), whereas others say that revealing an item leads to a change in the recognition decision criterion (e.g., Hicks & Marsh, 1998;Niewiadomski & Hockley, 2001). The increased familiarity explanations rely on the idea that, as long as the participants do not realize the source of the familiarity, they can misattribute it to having studied the word (e.g., Whittlesea & Williams, 2001).…”
mentioning
confidence: 99%
“…This memory illusion, the revelation effect, has been observed across a wide variety of conditions. Incidental tasks have included viewing the recognition probe in fragmentary or distorted form, typing it backward, or counting syllables and vowels (Luo, 1993;Watkins & Peynircioǧlu, 1990;Westerman & Greene, 1998). The task need not even involve the recognition probe directly; the illusion is produced by anagrams of unrelated words and number strings, arithmetic problems, and memory span tests (Bornstein & Neely, 2001;Verde & Rotello, 2003;Westerman & Greene, 1996.…”
mentioning
confidence: 99%